The Effect of Screen Media Use on School Performance at SMA Negeri 4 Binjai City - Tarigan, Jovanka Theresia; Elizabeth, Monalisa; Lumbantobing, Christina JR. Esmaralda (Jurnal Pendidikan Indonesia, 2025)
The pervasive use of screen media among high school students has raised concerns about its impact on academic performance. While digital devices offer educational benefits, excessive use for entertainment may negatively affect learning outcomes. This study aimed to analyze the effect of screen media use on school performance among students at SMA Negeri 4 Binjai City. An observational analytical study with a cross-sectional design was conducted in July 2025 involving 240 students selected through proportional stratified random sampling. Data on screen media types, usage duration, and activities (learning, movie watching, gaming, social media) were collected using validated questionnaires, while academic achievement was measured using school report cards. The chi-square test was used for data analysis with a significance level of p < 0.05. The majority of respondents (61.3%) used screen media for extended durations (>2 hours daily). Smartphones were the most prevalent device (82.5%). Significant correlations were found between screen media usage and academic achievement, particularly for duration (p = 0.000), movie watching (p = 0.000), gaming (p = 0.000), and social media use (p = 0.000). Learning activities through screen media showed a positive correlation with better academic performance (p = 0.001). Screen media usage patterns significantly affect students' academic achievement. High-duration usage and entertainment-oriented activities are associated with lower school performance, while educational use correlates with better outcomes. These findings highlight the need for balanced screen time management and guided media usage in educational settings.